Design of spectral amplitude coding optical code-division multiple-access system using random diagonal codes - Fadhil, H. A.; Syed Alwee Aljunid, Syed Junid; R. Badlishah, Ahmad (Fachverlag Schiele & Schoen GmbH, 2009)
Link to publisher's homepage at http://joc-online.schiele-schoen.de